The Dark Tower : The Wind Through the Keyhole - VIII - King, Stephen 1947- (New York : Scribner, 2012)
Returns to the rich landscape of Mid-World in a story within a story about gunslinger Roland Deschain, who while investigating a murderous shape-shifter interviews a terrified teen who has witnessed the creature's most recent killing.
Keywords: Roland (Fictional character) -- Fiction; Fantasy fiction